Revised Prasad and Kuppuswamy socioeconomic scales for India in 2024: Methods and Updates - Ahmad, Absar; Faizi, Nafis; Siddiqui, Nazneen Aiman (Indian Journal of Community Health, 2024)
Socioeconomic scales are vital to public health research to measure associations and impacts on health. BG Prasad classification and the Kuppuswamy scales are two commonly used socio-economic scales for India as they are cost-effective and efficient. While BG Prasad classification is based on per capita family income, Kuppuswamy also measures education and occupation of the family head in addition to monthly family income. Since income is a dynamic entity affected by economic changes such as inflation and cost of consumption, there is a need to update the Prasad and Kuppuswamy classification. This research updates both the classifications as per the latest consumer price index values for January 2024. The research also discussed the steps to update the classifications for future use.